2014
DOI: 10.1037/a0030930
|View full text |Cite
|
Sign up to set email alerts
|

The use and limitations of attachment theory in child psychotherapy.

Abstract: Attachment theory and research has proliferated in recent years, spawning new ideas and applications to child therapy. Some of those interventions are creative and useful and rest on solid theory and research, whereas others derive from tenuous assumptions. As an important developmental construct, attachment plays a role in every therapy, but defining that role can be difficult. Therapists must recognize the significance of attachment in treatment but not at the expense of recognizing and treating other issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 73 publications
(145 reference statements)
1
25
0
Order By: Relevance
“…This study found child neglect which is a byproduct of spousal conflict can have negative influence on the early childhood education. The results from this study confirm the notion that spousal conflict weakens parent-child bond (Klausli & Owen, 2011), which usually develops multifaceted types of emotional dysregulation (Kim & Cicchetti, 2010;Zilberstein, 2014) and belligerent behaviours. Ogundele (2018) posits that these behaviours can encumber learning, constrain access to normal school activities and social prospects, and require a substantial quantity of both manpower and financial expenses to effectively manage them.…”
Section: Academic Challengessupporting
confidence: 85%
“…This study found child neglect which is a byproduct of spousal conflict can have negative influence on the early childhood education. The results from this study confirm the notion that spousal conflict weakens parent-child bond (Klausli & Owen, 2011), which usually develops multifaceted types of emotional dysregulation (Kim & Cicchetti, 2010;Zilberstein, 2014) and belligerent behaviours. Ogundele (2018) posits that these behaviours can encumber learning, constrain access to normal school activities and social prospects, and require a substantial quantity of both manpower and financial expenses to effectively manage them.…”
Section: Academic Challengessupporting
confidence: 85%
“…Adoption and attachment experts propose that children with a history of neglectful caregiving can catch up developmentally and overcome social‐emotional and behavioral challenges when they are in relationships with emotionally attuned and responsive adults (Brodzinsky, ; Purvis et al, ; Siegel & Hartzell, ; Zilberstein, ). CPRT focuses on the primacy of a secure parent–child relationship as the agent of change.…”
Section: Discussionmentioning
confidence: 99%
“…Children can overcome early attachment hardships and move toward healthy functioning when their caregivers provide emotionally responsive caregiving (Zilberstein, ). Interventions that focus on building a secure parent–child relationship by helping parents attune, understand, and respond to their child's distress are essential for adopted children with a history of attachment disruptions to help them heal from their early adverse experiences (Carnes‐Holt & Bratton, ; Hughes, ; Purvis et al, ; Siegel & Hartzell, ).…”
Section: Attachment Needs Of Adoptive Familiesmentioning
confidence: 99%
“…Complex trauma can be understood as a set of experiences of cumulative, chronic and prolonged traumatic events, most often of an interpersonal nature, involving primary caregivers and frequently arising in early childhood or adolescence ( Courtois, 2004 ; Cook et al, 2005 ). Maltreatment experiences may include: severe neglect; exposure to domestic violence; intensive, painful medical conditions; and physical and sexual abuse ( Zilberstein, 2014 ). Often, children suffering from complex trauma face a combination of these experiences ( Ford et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%